1985
DOI: 10.1007/bf00744204
|View full text |Cite
|
Sign up to set email alerts
|

Structural and related functional changes in sarcoplasmic reticulum induced by long-chain fatty acids

Abstract: The effect of palmitic and oleic acids on Ca2+-ATPase activity in coupled preparations of sarcoplasmic reticulum isolated from rabbit hind leg muscle have been compared with their effects on vesicles uncoupled with Ca2+ ionophore, A23187. Palmitate at 2 microM X mg protein-1 has no significant effect on enzyme activity and does not uncouple catalytic activity from calcium accumulation within the vesicles. Oleic acid at 1 microM X mg protein-1 uncouples the vesicles, whereas 2 microM X mg protein-1 completely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1986
1986
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Stimulation of the purified enzyme in the latter studies, however, occurred at oleic and linoleic acid concentrations of 10-6-105 M. In the current studies, those fatty acids which were significantly active produced inhibition of enzyme activity at concentrations as low as 10-7-10-8 M. It should be pointed out that in some-reports of Ca2+-ATPase in situ in biological membranes, e.g. striated muscle sarcoplasmic reticulum (Munkonge et al, 1985) or human red cell (Wetzker et al, 1983), oleic acid at 106--10-5 M has previously been found to be inhibitory.…”
Section: Discussioncontrasting
confidence: 46%
“…Stimulation of the purified enzyme in the latter studies, however, occurred at oleic and linoleic acid concentrations of 10-6-105 M. In the current studies, those fatty acids which were significantly active produced inhibition of enzyme activity at concentrations as low as 10-7-10-8 M. It should be pointed out that in some-reports of Ca2+-ATPase in situ in biological membranes, e.g. striated muscle sarcoplasmic reticulum (Munkonge et al, 1985) or human red cell (Wetzker et al, 1983), oleic acid at 106--10-5 M has previously been found to be inhibitory.…”
Section: Discussioncontrasting
confidence: 46%
“…Compounds such as dansyl propranolol (Lee et al, 1983) and fatty acids (Froud et al, 1986b;Munkonge et al, 1985;Simmonds et al, 1982) can cause inhibition at high concentrations. At lower concentrations, however, oleic acid has been found to stimulate ATPase activity; the effect being particularly marked for the ATPase reconstituted into bilayers of phospholipids with short fatty acyl chains, such as dimyristoleoylphosphatidylcholine (DMPC, C 1 4 ) (Froud et al, 19866).…”
Section: Introductionmentioning
confidence: 99%